Nanopartículas de Pt suportadas em Al2O3 e CeO2-Al2O3: síntese e caracterização de catalisadores aplicados à reação de deslocamento gás-água - Ribeiro, Renata Uema (2011)
Colloidal Pt nanoparticles were synthesized according to an adapted procedure from Song and co-workers [1], which it was based on the reduction of dihydrogen hexachloroplatinate by ethylene glycol in a basic solution, but using two PVP/Pt = 0,2 and 10 ratio. Both the ratio lead to monodisperse platinum nanoparticles with similar sizes (2.0 and 2.8 nm). Colloidal Pt nanoparticles solutions were incorporated into alumina during sol-gel synthesis and showed different stabilities when submitted to thermal treatment in synthetic air, He and H2 atmospheres. PVP/Pt ratio added to nanoparticles after synthesis was the main parameter considered to the stability of the particles on the support. Using a minor PVP/Pt ratio lead to particles agglomerates during calcinations step in synthetic air. On the other hand, when an excess of PVP was used stable and disperse particles were obtained during a severe thermal treatment. The anchoring of particles into support during incorporation stage could be the most plausible explanation for this. Platinum nanocatalysts supported on alumina and ceriaalumina showed catalytic activity for the water gas shift reaction. CO conversion data indicated that the increasing of CeO2 loading of 12 to 20% lead to an improvement in the catalytic activity. XPS measurements after pre-treatment in H2 confirmed the presence of Pt+on the catalyst surface containing ceria, suggesting some metal-support interaction. In situ characterization techniques allowed to a better understanding of species involved into water gas shift reaction mechanism. Through X-ray absorption near edge structure in the Pt edge measurements showed reduced Pt during reaction for all catalysts, suggesting that similar electronic density of sites was present. This was also observed in CO adsorbed DRIFTS measurements. Nevertheless, XANES spectra in the Ce edge showed some changes in oxidation state of Ce during the reaction, indicating the occurrence of redox mechanism, mediated by ceria. In situ DRIFTS experiments showed little concentrations of formates and carbonates species on the catalyst surface during the reaction, suggesting that more than one mechanism may occur simultaneously.